Condensed Mode Cooling for Ethylene Polymerization: Part V—Reduction of the Crystallization Rate of HDPE in the Presence of Induced Condensing Agents. Issue 9 (3rd April 2019) - Andrade, Fabiana N.; Fulchiron, René; Collas, Franck; McKenna, Timothy F. L.
Abstract: The crystallization of high‐density polyethylene (HDPE) alone, and in the presence of n‐hexane (a common induced condensing agent [ICA]) is studied using differential scanning calorimetry. The presence of a noncrystallizable ICA which is partially soluble in the amorphous phase of HDPE reduces the rate of crystallization. This is reflected by a shifting of the crystallization and melting peaks of HDPE to lower temperatures when the ICA concentration in the medium increases. It is also observed that the rate of crystallization of HDPE can be very slow when the ratio of ICA to HDPE increases from zero. This behavior is useful to better understand the physical effects that can potentially occur at the beginning of the gas phase polymerization of ethylene, and suggests that the crystallization of the nascent polymer, and thus the properties of the polymer in the reactor will be quite different from those of the powder at later stages of the reaction when running in condensed mode. Abstract : The crystallization rate of high‐density polyethylene is studied using differential scanning calorimetry, and it is shown that the presence of an alkane (or induced condensing agent) reduces the rate of polymer crystallization, in some cases, to timescales on the order of minutes under conditions characteristic of lab‐scale experiments.